Veganism a Fashion Trend or Food as a Medicine - Jovandaric, Miljana Z. (IntechOpen, 2021)
Veganism is a way of eating and living that avoids using animals and their products for food, clothing, and other purposes. Vegans do not consume meat, fish, seafood, eggs, honey, and dairy products, nor do they wear or carry items made of fur, wool, leather, and other materials of animal origin. Many vegans also avoid animal-tested products.